Carbon and 2D nanomaterial smart hydrogels for therapeutic applications - Xiang Shunyu; Ménard-Moyon Cécilia; Bianco Alberto (Nanotechnology Reviews)
Smart hydrogels, also known as environmentally responsive hydrogels, are a kind of intelligent polymer-based material network undergoing deformation and phase changes under external environmental stimuli. These special physicochemical properties make hydrogels great molecular systems for applications in controlled drug release. Particularly, hydrogels loaded with nanomaterials show strong potential in terms of mechanical properties and environmental responsiveness. In this context, the use of carbon and two-dimensional (2D) nanomaterials has attracted widespread attention, as they can trigger drug release. This review provides an overview of the current progress in the design of biocompatible and environmentally responsive hydrogels containing carbon and 2D nanomaterials, focusing on their preparation, properties, and advantages for drug release to treat different diseases such as cancer, diabetes, and inflammation.